Sequenciamento genético à luz do Direito: da digitalização da vida à identidade autêntica - Patricia Gazire De Marco (2019)
This thesis is focused on Personalized Medicine, and specifically the role that genetic testing plays in promoting better patient care. The thesis aims to analyses an ethical and medically accepted and rational ethics guideline on disclosure of genetic test results. Although there are well accepted principles that guide genetic research and use of genetic information in clinical practice, there are still gaps in the regulatory framework of genetics-based results disclosure generated by these tests, whether relevant to the tested phenotype or incidental findings. Issues range across many aspects and include, among others informed consent, the right to know or refusal to know, data privacy, confidentiality, providers of genetic counseling, the impact on health care professional‘s duties for the counseled individual and other family members, the impact of genetic data in affected and healthy, high-risk individuals on the health care system. These and additional related issues, need to be discussed and updated in an ongoing manner to keep up with scientific and medical progress. These issues present a major challenge for the protection of human rights, as they directly impact the privacy, well-being of the patient while maintaining the patent‘s rights for confidentiality, and ensuring the ability of all individuals for equal and timely access to genetics based analyses in order to maximize the ability to benefit from the progress and hope that genetics provides to personalized health care. The legal aspects that govern the laws and regulations should consider the patient‘s rights as the primary factor, while balancing the effects of these regulations on their families, society, the medical community, health insurers and law makers at the national level. Given the reality of personalized medicine and the rate of progress that science and medicine are evolving, there needs to be an action taken by the regulators to ensure that all aspects of clinical use of these novel tools are used in a manner that is aligned with preserving patient‘s rights and privacy.